The origins of the Second World War in Europe - Bell, P. M. H. (Philip Michael Hett), 1930- (New York : Longman, 1997)
Investigates the European origins of World War II, looking at traditional explanations for the conflict, analyzing the underlying ideological, economic, and strategic forces of the 1930s, and including a history of events from 1932 through June 1941.
Includes bibliographical references (p. 342-351) and index.
Adult
Keywords: World War, 1939-1945 -- Causes; World War, 1939-1945 -- Causes; Europe -- Politics and government -- 1918-1945.; Europe -- Politics and government